Betalain exerts cardioprotective and anti-inflammatory effects against the experimental model of heart failure. (December 2021) - Gao, Y; Liang, X; Tian, Z; Ma, Y; Sun, C
Betalain is a natural plant pigment known to elicit various biological activities. However, studies on the protective effect of betalain against heart failure have not reported yet. The experimental model of heart failure was created in Wistar rats using isoproterenol (ISO). The animals were randomly assigned into four groups such as sham-control, ISO-induced heart failure, betalain pretreated before ISO induction (50 mg/kg/day), and betalain drug control group were maintained for 6 weeks. At the end of the experimental period, anti-oxidant enzymes, inflammatory markers, matrix proteins, cardiac-specific markers, and micro RNAs were elucidated using RT-PCR, and ELISA analysis. The results demonstrated that the rats induced with ISO displayed an abnormality in cardiac functions, increased oxidative stress markers ( p < 0.01), inflammatory cytokines ( p < 0.01) while abrogated the expression of miR-18a, and increased miR-199a. While betalain pre-treated rats prevented the cardiac failure significantly ( p < 0.01) with improved anti-oxidant enzymes, abrogated the inflammatory signals with restored matrix proteins, cardiac biomarker genes, and attenuated miR-423 and miR-27 compared to heart failure rats. The results of the study suggest that the betalain treatment protected the hearts from failing via microRNA mediated activation the anti-inflammatory signaling and restoring the matrix protein modulation.